New challenge for social inclusion - marine product processing development of mussel farming in the Baltic sea region - Ozolina, Zaiga; Sloka, Biruta (University of Latvia, 2020)
Product recycling opportunities that potentially increase the value of the initial product create interest in creating and developing a field. Seafood is demanded product in the world but creating a higher value of the product the value of it can be increased and in many countries it helped to solve social problems with food provision and employment. Aim of research analysis of area for mollusc farming, and mollusc-processing options to explore opportunities for development of the field. By analysing views of public administrators, entrepreneurs and researchers in selected Baltic Sea Region countries. Based on expert viewpoint (public administrators, entrepreneurs and researchers that participated in the survey), the study summarizes aspects of seafood re-processing that may affect the potential for shellfish development in the Baltic Sea region and whether educational measures can contribute to the development of processed seafood in the Baltic Sea Region. Research methods used: Scientific publication studies on mussel farming development and marine product processing supporting and braking factors, survey of different stakeholders in mussel farming – public administrators, entrepreneurs and researchers; expert interviews. For evaluation of different aspects affecting marine product processing from mussel farming evaluation scale 1 – 10 was used, where 1 – do not affect; 10 – affect in great extent. Data obtained in the survey were analysed with indicators of descriptive statistics, cross-tabulations by gender, education level, age group and country, analysis of variance – ANOVA, correlation analysis, and factor analysis. From the experts' point of view, the important aspects that could affect the processing of marine products in mussel farming in the Baltic Sea region were indicated as government support, education including informal education, human resources as well as marketing events. The results were statistically different by age group and by country. Experts who evaluated aspects of education as a less important factor affecting the development of marine product processing rated the development potential of marine product processing over the next 10 years lower.
Keywords: social inclusion; marine product processing; marketing tools; mussel farming; survey; Research Subject Categories::SOCIAL SCIENCES::Business and economics